Community Participation in Education in the Digital Age in Indonesia - Mohamad Ardin Suwandi; Heinrich Rakuasa (International Journal of Educatio Elementaria and Psychologia, 2024)
In the digital age, community participation in education has become increasingly vital for enhancing learning outcomes in Indonesia. This research explores how digital tools can transform traditional forms of community involvement, allowing for greater flexibility and engagement among parents, students, and local communities. Utilizing a literature study method, the research analyzes secondary data from credible sources, employing thematic analysis to identify key themes related to community participation in education. The findings reveal that while digital platforms facilitate improved communication and involvement, significant challenges remain due to the digital divide, particularly in rural areas where access to technology is limited. Additionally, the study highlights the importance of understanding cultural contexts to design educational programs that resonate with local populations. In conclusion, the research emphasizes the need for policies that promote digital literacy and equitable access to technology, fostering collaboration among schools, families, and communities to create a more inclusive educational system that meets the diverse needs of all learners in Indonesia.